Ответ:
7
Объяснение:
59/9-13/4 = 236/36-117/36 = 119:36, 36:17 = 119/17 = 7
5 + 2/17
(59/6 - 13/4) * 36/17 = ((59*4 - 13*6)/24) * 36/17 = ((236-78)/24) * 36/17 = (158/24)* 36/17 = (158 * 36) / (24 * 17) = (58 * 3) / (2 * 17) = (29 * 3) / 17 = 87/17 = 5 + 2/17
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
7
Объяснение:
59/9-13/4 = 236/36-117/36 = 119:36, 36:17 = 119/17 = 7
Ответ:
5 + 2/17
Объяснение:
(59/6 - 13/4) * 36/17 = ((59*4 - 13*6)/24) * 36/17 = ((236-78)/24) * 36/17 = (158/24)* 36/17 = (158 * 36) / (24 * 17) = (58 * 3) / (2 * 17) = (29 * 3) / 17 = 87/17 = 5 + 2/17